GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 309 species occurrences available in GBIF matching the query: TaxonKey: Peumus boldus Molina. The dataset includes 309 records from 45 constituent datasets: 25 records from Phanerogamic Botanical Collections (S). 2 records from University of Vienna, Institute for Botany - Herbarium WU. 21 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from SPF - Herbário da Universidade de São Paulo. 3 records from SANT herbarium vascular plants collection. 8 records from Herbario Universidad de Antioquia (HUA). 4 records from MBM - Herbário do Museu Botânico Municipal. 1 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 2 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 10 records from Australia's Virtual Herbarium. 2 records from UCBG TAPIR Provider. 1 records from CONN. 2 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 3 records from HPBR - Herbário Padre Balduino Rambo. 4 records from NMNH occurrence DwC-A. 5 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 8 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 8 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 49 records from Tropicos Specimen Data. 10 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Jardín Botánico de Córdoba: Herbarium COA. 1 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 3 records from Institut Botanic de Barcelona, BC. 6 records from NSW herbarium collection. 4 records from Herbarium Berolinense. 1 records from DSMZ Collection on Plant Cell Cultures. 1 records from Institut Botanic de Barcelona, BC-Histórico. 3 records from Harvard University Herbaria. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from USF Herbarium. 16 records from Field Museum of Natural History (Botany) Seed Plant Collection. 1 records from Botany Division, Yale Peabody Museum. 57 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from HUEG - Herbário da Universidade Estadual de Goiás. 1 records from UFACPZ - Herbário da Universidade Federal do Acre. 21 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Botany (UPS). 1 records from Museu de Ciències Naturals de Barcelona: BGJBB. 2 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 1 records from SLUI - Herbário Rosa Mochel. 2 records from Allan Herbarium (CHR). 10 records from SysTax - Botanical Gardens. 1 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 1 records from Instituto de Botánica Darwinion. 1 records from UFMT - Herbário UFMT.
Keywords: GBIF; biodiversity; species occurrences